Early Mississippian evaporites of coastal tropical wetlands. Issue 7 (12th April 2018) - Millward, David; Davies, Sarah J.; Williamson, Fiona; Curtis, Rachel; Kearsey, Timothy I.; Bennett, Carys E.; Marshall, John E. A.; Browne, Michael A. E.
Abstract: Extensive evaporites in Lower Mississippian successions from palaeoequatorial regions are commonly used as evidence for an arid to semi‐arid palaeoclimate. However, in this article, detailed studies of evaporites and their context refute this interpretation. Detailed sedimentological and petrographical analysis of the Lower Mississippian of northern Britain, is combined with archived log data from more than 40 boreholes across southern Scotland, northern England and Northern Ireland, and published literature from Canada. Two key cores from the Tweed Basin and the northern margin of the Northumberland – Solway Basin contain 178 evaporite intervals and reveal twelve distinct forms of gypsum and anhydrite across seven facies that are associated with planar laminated siltstone and intercalated thin beds of ferroan dolostone. Nodular gypsum and anhydrite, typically in intervals <1 to 2 m thick, are integral components of the succession. Nodular evaporite occurs within about 1 m of a palaeosurface, but most evaporite deposits represent ephemeral brine pans to semi‐permanent hypersaline lakes or salinas on a floodplain that was subjected periodically to storm surges introducing marine waters. Formation of evaporites under a strongly seasonal climate in a coastal wetland is supported by palaeosol types and geochemical proxies, and from palaeobotanical evidence published previously. Although 65% of modern equatorial areas experience a strongly seasonal climatic regime, salinas and sabkhas are a minor component today in comparison with the evidence from these Lower Mississippian successions. This implies that the earliest terrestrial environments were complex and dynamic, providing a diverse range of habitats in which the early tetrapods became terrestrialized and represent a setting that is rarely preserved in the geological record.